2008
DOI: 10.1063/1.2912058
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations as dissociation mechanism in bichromatically driven diatomic molecules

Abstract: We discuss the influence of periodic orbits on the dissociation of a model diatomic molecule driven by a strong bichromatic laser fields. Through the stability of periodic orbits, we analyze the dissociation probability when parameters, such as the two amplitudes and the phase lag between the laser fields, are varied. We find that qualitative features of dissociation can be reproduced by considering a small set of short periodic orbits. The good agreement with direct simulations demonstrates the importance of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In particular, it has been demonstrated that the transition to chaos is connected with the overlapping of vibrational-rotational nonlinear resonances and appears at rather low radiation field intensities [29,30]. The dissociation dynamics of a diatomic molecule driven by a bichromatic field has been analyzed in terms of periodic bifurcations [31]. For polyatomic molecules, it has been demonstrated that classical stationary objects, e.g., equilibria, periodic orbits, tori or manifolds, act as organizing structures for the quantum mechanical eigenstates and their identification is needed for the spectral assignment of highly excited levels [32].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been demonstrated that the transition to chaos is connected with the overlapping of vibrational-rotational nonlinear resonances and appears at rather low radiation field intensities [29,30]. The dissociation dynamics of a diatomic molecule driven by a bichromatic field has been analyzed in terms of periodic bifurcations [31]. For polyatomic molecules, it has been demonstrated that classical stationary objects, e.g., equilibria, periodic orbits, tori or manifolds, act as organizing structures for the quantum mechanical eigenstates and their identification is needed for the spectral assignment of highly excited levels [32].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noticed that for increasing frequency bandwidths and amplitudes of the external field, additional Fourier components have to be taken into account in the approximation made in Eq. (11).…”
Section: An Isolated Nonlinear Resonance Is Defined Bymentioning
confidence: 99%
“…When the oscillator is subjected to an external driving field, a particle in the bound region can escape to the unbound region and this transition corresponds to the dissociation of the molecule. The dissociation occurs through chaotic routes, * eflima@rc.unesp.br † tarciusnramos@gmail.com ‡ regydio@rc.unesp.br as a result of the destruction of Kolmogorov-Arnold-Moser (KAM) tori in phase-space for increasing values of the field amplitude [3,20].Several works have investigated the classical dissociation dynamics within the driven Morse model [1][2][3][4][5][6][7][8][9][10][11][12][21][22][23][24][25][26]. Also, many quantum-classical comparisons have been performed and correspondences between the two theories have been found in some situations [27][28][29][30][31][32][33][34][35][36][37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of such as studies can be found in Refs. [23][24][25][26][27][28][29][30][31][32][33]. Furthermore, classical studies in microscopic systems have revealed themselves as a power tool to understand quantum mechanical results in many cases (see e.g.…”
Section: Introductionmentioning
confidence: 99%